Health Benefits, Applications, and Analytical Methods of Freshly Produced Allyl Isothiocyanate - Walaa Alibrahem; Duyen H. H. Nguyen; Nihad Kharrat Helu; Florence Tóth; Péter Tamás Nagy; János Posta; József Prokisch; Csaba Oláh (Foods)
Allyl isothiocyanate (AITC) is a low-molecular-weight natural chemical predominantly obtained from the autolysis of sinigrin, a glucosinolate found in cruciferous vegetables like mustard, horseradish, and wasabi. AITC has sparked widespread interest due to its various biological actions, which include strong antioxidant, anti-inflammatory, antibacterial, and anticancer capabilities. This compound offers promising potential in several fields, particularly in food preservation, medicine, and enhancing food quality through natural means. AITC’s effectiveness against a broad spectrum of microorganisms, including foodborne pathogens and spoilage agents, makes it an attractive natural alternative to synthetic preservatives. The potential to extend the shelf life of perishable foods makes AITC an important tool for food production, meeting rising customer demand for natural additives. In addition to its antimicrobial effects, AITC demonstrates significant anti-inflammatory activity, reducing levels of pro-inflammatory cytokines and modulating key signaling pathways, which could make it valuable in managing chronic inflammatory conditions. Furthermore, emerging research highlights its potential in cancer prevention and treatment, as AITC has been demonstrated to induce apoptosis and inhibit cell increase in several cancer cell lines, offering a natural approach to chemoprevention. This review delves into the chemical structure, metabolism, and bioavailability of freshly produced AITC, providing a comprehensive overview of its beneficial properties. Challenges related to AITC’s volatility, dosage optimization, and regulatory considerations are also discussed, alongside future research directions to enhance the stability and efficacy of AITC-based formulations. The findings underscore AITC’s role as a versatile bioactive compound with known potential to support human health and the sustainable food industry.